2013
DOI: 10.1093/eurheartj/eht459
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double-blind, placebo-controlled, multicentre study to assess haemodynamic effects of serelaxin in patients with acute heart failure

Abstract: AimsThe aim of this study was to evaluate the haemodynamic effects of serelaxin (30 µg/kg/day 20-h infusion and 4-h post-infusion period) in patients with acute heart failure (AHF).Methods and resultsThis double-blind, multicentre study randomized 71 AHF patients with pulmonary capillary wedge pressure (PCWP) ≥18 mmHg, systolic blood pressure (BP) ≥115 mmHg, and estimated glomerular filtration rate ≥30 mL/min/1.73 m2 to serelaxin (n = 34) or placebo (n = 37) within 48 h of hospitalization. Co-primary endpoints… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
1
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 108 publications
(101 citation statements)
references
References 17 publications
3
92
1
5
Order By: Relevance
“…Central hemodynamic studies of serelaxin in patients with AHF showed that serelaxin decreased the mean pulmonary artery pressure and pulmonary capillary wedge pressure, indicating cardiac unloading. 9,10 However, in these studies, serelaxin did not increase cardiac index. An increase in cardiac index as an explanation for the increase in RPF with serelaxin in this study is, therefore, unlikely.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Central hemodynamic studies of serelaxin in patients with AHF showed that serelaxin decreased the mean pulmonary artery pressure and pulmonary capillary wedge pressure, indicating cardiac unloading. 9,10 However, in these studies, serelaxin did not increase cardiac index. An increase in cardiac index as an explanation for the increase in RPF with serelaxin in this study is, therefore, unlikely.…”
Section: Discussioncontrasting
confidence: 54%
“…The following formulas were used: infusion rate (mg/h) for IOTH=1.2×eGFR (mL/min) and infusion rate (mg/h) for PAH=5.5×eGFR (mL/min). For pooled time intervals (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) hours, 0-24 hours, and 24-28 hours), plasma concentration in the above formula was replaced by the time-weighted average plasma concentration (area under the curve divided by time). Baseline plasma clearance was derived using the 0-hour IOTH/ PAH concentration measurement.…”
Section: Primary End Pointsmentioning
confidence: 99%
“…Cardiac filling pressures, considered the driving force behind pulmonary congestion, have shown potential to decrease rapidly following aggressive AHF treatment initiation,27, 28 while pulmonary decongestion can be assessed in real time with LUS 14. Echo‐derived filling pressures and LUS have also displayed prognostic significance prior to discharge, making them potential treatment targets during AHF hospitalizations 16, 17, 29.…”
Section: Discussionmentioning
confidence: 99%
“…10 A separate study addressed the hemodynamic effects of serelaxin in patients with AHF (NYHA III-IV class) and SBP >115 mmHg. 22 Serelaxin was administered at 30μg · kg -1 · day -1 for 20 h and hemodynamic parameters were monitored for 24 h and blood pressures for 44 h. Compared with the placebo-treated patients (n=37) receiving standard therapy, treatment with serelaxin exerted a rapid (<30 min) hemodynamic improvement measured by a reduction in pulmonary capillary wedge-pressure (PCWP), pulmonary artery pressure (PAP), SVR and pulmonary vascular resistance (PVR) without significant change in CI. Meanwhile, serelaxin administration improved renal function and reduced both SBP and diastolic blood pressure by 7-10 mmHg.…”
Section: Key Findings From the Clinical Trials On Serelaxinmentioning
confidence: 99%